The last ghetto : an everyday history of Theresienstadt - Hájková, Anna 1978- (Oxford University Press, 2020)
"The Last Ghetto is the first in-depth analytical history of a prisoner society during the Holocaust. Terezín (Theresienstadt in German) was operated by the Nazis between November 1941 and May 1945 as a transit ghetto for Central and Western European Jews before their deportation for murder in the East. Rather than depict the world of the prisoners as an atomized state of exception, it argues that the prisoner societies in the Holocaust are best understood as existing among the many versions of societies as we know them. This book challenges the claims of Holocaust exceptionalism and insisting that we view it with the same analytical tools as other historical events. The prisoner society Terezín produced its own social hierarchies, but the contents of categories such as class changed radically: seemingly small differences among prisoners could determine whether one ultimately lived or died. During the three and a half year of the ghetto's existence, prisoners created their own culture and habits, bonded, fell in love, and forged new families. The shared Jewishness of the prisoners was not the basis of their identities, but rather, prisoners embraced their ethnic origin. Based on extensive archival research in nine languages, The Last Ghetto is a transnational, cultural, social, gender, and organizational history of Terezín, revealing how human society works in extremis"--